Pleural Diseases in Connective Tissue Diseases - Guo, Hui; Iqbal, Beenish; Rahman, Najib M. (Seminars in Respiratory and Critical Care Medicine, 2024)
Connective tissue diseases (CTD) are heterogeneous, immune-mediated inflammatory disorders often presenting with multiorgan involvement. With the advent of high-resolution computed tomography, CTD-related pleuritis—pleural thickening and effusion—is now increasingly recognized early in the disease trajectory. The natural history of CTD-related pleural effusions varies from spontaneous resolution to progressive fibrothorax with ventilatory impairment. Treatment of the underlying CTD is necessary to manage the pleural disease. Depending on the degree of symptom burden and physiological insult, specific treatment of pleural disease can include monitoring, repeated aspirations, systemic anti-inflammatory medication, and surgical decortication.
Keywords: connective tissue disease; collagen vascular disease; pleural disease; pleuritis; pleural effusion; pleural thickening; pneumothorax